Rescue subthalamic stimulation after unsatisfactory outcome of pallidal stimulation in Parkinson's disease: a case series and review - Zeng, Zhitong; Huang, Peng; Lin, Zhengyu; Pan, Yixin; Wan, Xiaonan; Zhang, Chencheng; Sun, Bomin; Li, Dianyou (Frontiers in Aging Neuroscience, 2024)
Background: Subthalamic nucleus (STN) and globus pallidus interna (GPi) are two main structures primarily targeted by deep brain stimulation (DBS) to treat advanced Parkinson's disease (PD). A subset of cases with unsatisfactory outcome may benefit from rescue DBS surgery targeting another structure, while these patients' characteristics have not been well described and this phenomenon has not been well reviewed.In this monocentric retrospective study, patients with PD with unsatisfactory outcomes after initial bilateral GPi DBS who subsequently underwent rescue bilateral STN DBS were included. A mini-review of the current literature reporting the clinical outcome of rescue DBS surgeries was conducted.Results: Eight patients were identified and six of them were included in this study. The rescue STN DBS was performed 19.8 months after the initial GPi DBS. 8.8 months after the rescue STN DBS, patients showed a significant off-medication improvement of 29.2% in motor symptoms compared to initial GPi DBS. Non-motor symptoms and the health-related quality of life were also significantly improved.Our findings suggest that the rescue STN DBS may improve off-medication motor and non-motor symptoms, and quality of life in patients with failure of initial GPi DBS. The minireview of the current literature showed that the target switch from GPi to STN was mostly due to poor initial outcomes and was performed by target substitution, whereas switch from STN to GPi was mostly due to a gradual waning of benefits, long-term axial symptoms, dyskinesia and dystonia, and was performed by target addition.